An ultrapotent pan-β-coronavirus lineage B (β-CoV-B) neutralizing antibody locks the receptor-binding domain in closed conformation by targeting its conserved epitope. Issue 9 (23rd September 2021) - Liu, Zezhong; Xu, Wei; Chen, Zhenguo; Fu, Wangjun; Zhan, Wuqiang; Gao, Yidan; Zhou, Jie; Zhou, Yunjiao; Wu, Jianbo; Wang, Qian; Zhang, Xiang; Hao, Aihua; et al.
Abstract: New threats posed by the emerging circulating variants of SARS-CoV-2 highlight the need to find conserved neutralizing epitopes for therapeutic antibodies and efficient vaccine design. Here, we identified a receptor-binding domain (RBD)-binding antibody, XG014, which potently neutralizes β-coronavirus lineage B (β-CoV-B), including SARS-CoV-2, its circulating variants, SARS-CoV and bat SARSr-CoV WIV1. Interestingly, antibody family members competing with XG014 binding show reduced levels of cross-reactivity and induce antibody-dependent SARS-CoV-2 spike (S) protein-mediated cell-cell fusion, suggesting a unique mode of recognition by XG014. Structural analyses reveal that XG014 recognizes a conserved epitope outside the ACE2 binding site and completely locks RBD in the non-functional "down" conformation, while its family member XG005 directly competes with ACE2 binding and position the RBD "up". Single administration of XG014 is effective in protection against and therapy of SARS-CoV-2 infection in vivo . Our findings suggest the potential to develop XG014 as pan-β-CoV-B therapeutics and the importance of the XG014 conserved antigenic epitope for designing broadly protective vaccines against β-CoV-B and newly emerging SARS-CoV-2 variants of concern.